Răspuns: Demonstrația mai jos
Explicație pas cu pas:
Salutare!
[tex]\bf [(3^{11}+2\cdot 3^{11})^{2}:3^{23}+2^{0}]^{11}=[/tex]
[tex]\bf [(3\cdot 3^{11})^{2}:3^{23}+1]^{11}=[/tex]
[tex]\bf [( 3^{11+1})^{2}:3^{23}+1]^{11}=[/tex]
[tex]\bf [( 3^{12})^{2}:3^{23}+1]^{11}=[/tex]
[tex]\bf ( 3^{12\cdot 2}:3^{23}+1)^{11}=[/tex]
[tex]\bf ( 3^{24}:3^{23}+1)^{11}=[/tex]
[tex]\bf ( 3^{24-23}+1)^{11}=[/tex]
[tex]\bf ( 3^{1}+1)^{11}=[/tex]
[tex]\bf ( 3+1)^{11}=[/tex]
[tex]\bf 4^{11}=[/tex]
[tex]\bf (2^{2})^{11}=2^{2\cdot11}=2^{22}=[/tex]
[tex]\boxed{\boxed{\bf (2^{11})^{2} \implies patrat~perfect}}[/tex]
#copaceibrainly